Masculinities and gender relationships in university students. Faculty of social sciences. UNMSM, 2015 - León Pretel, Pricila (2017)
This study describes the types of masculinities presented by young university students in the Faculty of Social Sciences at San Marcos University. The concepts guiding the research are mainly three, exposed by RW. Connel (1995), P. Bourdieu (1990) and M. Kimmel (1994). The methodology is qualitative; we applied a questionnaire designed with the Likert scale to identify the intensity of belief in each statement. Forty students from the Academic Professional Schools of Sociology, Anthropology and History participated, their ages range from 20 to 23 years old. The main results show that the university students have some elements of emerging masculinities; keeping the main elements of hegemonic masculinity, such as: authority, power and dominion of the public sphere. However, the profile that describes them would already be influenced by participants’ academic training which includes training courses on gender issue that is transverse to the educational project designed for all specialties of the faculty.